Kom ons skryf 'n Psalm! - S. D. Snyman (Acta Theologica)
This article is a report on an exercise in Psalm writing performed by theological students in a course on the introduction, exegesis and theology of the Psalms. What was interesting and surprising was that, without a thorough knowledge of the literary genres used in the canonical Psalms, the students made use of genres like the individual lament, wisdom and psalms of trust. Little could be gained from the student-psalms of the setting in life (Sitz im Leben) of the psalms. Due to the personal nature of the psalms, the exact setting in life was even deliberately obscured. This should caution modern day researchers of the canonical Psalms to be mindful of the fact that the reconstruction of the setting in life of canonical psalms is indeed only a reconstruction of what we think might have been the setting in life.